Higienização das mãos em Centro de Material e Esterilização - Pires, Francine Vieira (2013)
This study addresses hand hygiene (HH) in the context of Materials and Sterilization Centers (MSC), hospital support units where patients are not present. Knowledge of the practice of HH in this unit is an important step in the development and validation of procedures related to HH. The general objectives in this study were: to analyze the practice of HH in an MSC. The specific objectives were: to identify the physical and material resources and the availability thereof with regard to HH in a MSC; to identify opportunities for HH for staff who work in a MSC; to assess compliance with HH procedures for staff who work in a MSC; to classify the HH techniques used for staff who work in a MSC. Exploratory, descriptive, cross-sectional, quantitative approach, performed in cooperation with the staff who work in a hospital MSC at a large university hospital in the city of Goiânia, Brazil. The targets of observation were the physical resources and raw materials available for HM. Data were collected in a period from July to November 2012 in two steps. Collection started with filling in a checklist using direct and non-participant observation of resources and supplies (soap, alcohol, etc.) available for HH, opportunities for HH and following standardized HH technique, followed by an interview of a subject where consent was obtained. It used descriptive statistics for frequency. The study was approved by a research ethics committee of the participating institiution and pertinent ethical guidelines were observed. The study included 33 workers, two without specific training in nursing. The study observed the availability of supplies, however a lack of systematic replacement resulted in the unavailability of certain materials, although the employee was empowered to perform the HH in a freely accessible, adjacent area. Some inadequate resources and procedures were observed, such as manual dispensers, recycled paper towels, drying hands on communal cloth cotton fabric towels, and wiping hands on clothes. Greater compliance with HH procedures in the different areas of the MSC was observed "at the start of the shift" and "after removing gloves." Observations in clean and restricted areas indicated that perhaps more consistency in establishing regular intervals of time should be established for workers to perform HH. Most workers reported having been trained on this subject, but compliance with HH technique was mostly irregular. Low use of alcohol-based hand sanitizer was observed, while it was always available. Most workers voiced concerns over which method for HH to choose for use in each situation. In the opinion of employees, availability of resources and supplies creates a favorable atmosphere for compliance with HH procedures, including personal factors cited, such as the recognition that the protection of the employee comes first, followed by the the protection of the equipment being sterilized or compliance with HH procedures. These results are similar to findings of studies in units where patients are present and places the MSC in the same position as to require additional training and monitoring of compliance with hand hygiene.